Molecular epidemiology and phenotypes of invasive methicillin-resistant vancomycin-intermediate Staphylococcus aureus in Taiwan - Wei-Yao Wang; Chen-Feng Chiu; Yuan-Ti Lee; Po-Ren Hsueh; Shih-Ming Tsao (Journal of Microbiology, Immunology and Infection, 2022)
Background: Patients with invasive infections caused by methicillin-resistant Staphylococcus aureus (MRSA), especially those with an elevated minimal inhibitory concentration (MIC) of vancomycin (VA), are likely to have treatment failure and poor outcomes. The aim of this study was to delineate and correlate the genotypes and phenotypes of clinical VA-intermediate S. aureus (VISA) from invasive infections in Taiwan. Methods: Between 2006 and 2010, a total of 670 non-duplicate MRSA isolates were collected from patients with invasive infections, mostly from blood, as part of a nationwide antimicrobial surveillance program named Tigecycline in vitro Surveillance in Taiwan. Among them, 10 (1.5%) VISA (VA MIC = 4 mg/L) isolates were identified. Molecular typing with staphylococcal cassette chromosome mec (SCCmec), multilocus sequence typing, staphylococcal protein A (spa), mec-associated hypervariable region (dru), accessory gene regulator (agr), and pulse-field gel electrophoresis, and phenotypic analysis including antibiotic susceptibility testing, gene encoding Panton-Valentine leukocidin (pvl), and superantigenic toxin profiles, were analyzed. Results: All but one isolate was defined as molecular health-care-associated MRSA: 6 as SCCmecIII-ST239-spa t037-agrI-dru7 (1 isolate) and dru14 (5 isolates), 2 as SCCmecII-ST5-spa t586-agrII-dru4, and one as SCCmecII-ST89-spa t3520-agrIII-dru7. One isolate was defined as SCCmecIV-ST59-spa t437-agrI-dru8, which was categorized as molecular community-associated MRSA. Five pulsotypes were identified; only one had a positive D-test and 3 were insusceptible to daptomycin (MIC ≧1 mg/L). Five isolates possessed sea-selk-selq, among them 4 belonged to SCCmecIII-ST239-spa t037-agrI. Conclusion: In this study, VISA was rarely isolated from invasive MRSA infections, and most cases harbored limited genotypes and corresponding phenotypes.